Azithromycin alleviates the severity of rheumatoid arthritis by targeting the unfolded protein response component of glucose‐regulated protein 78 (GRP78). (2nd December 2021) - Zhang, Yongli; Ge, Luna; Song, Guanhua; Zhang, Ruojia; Li, Shufeng; Shi, Haojun; Zhang, Hongchang; Li, Yi; Pan, Jihong; Wang, Lin; Han, Jinxiang
Abstract : Background and Purpose: Azithromycin is a macrolide antibiotic with anti‐inflammatory properties. We aim to substantiate the treatment potential of azithromycin in rheumatoid arthritis. Experimental Approach: Gene expression profiles were collected by RNA sequencing and the effects of azithromycin were assessed by in vitro and i n vivo assays on the effects of azithromycin‐mediated blockade of glucose‐regulated protein 78 (GRP78). Anti‐inflammatory activity of azithromycin was measured in fibroblast‐like synoviocytes from rheumatoid arthritis patients and in collagen‐induced arthritis in DBA/1 mice. Characterization of the binding of azithromycin to GRP78 was performed using drug affinity responsive target stability, proteomics and cellular thermal shift assays. Azithromycin‐mediated inhibition of GRP78 and its relationship to its anti‐arthritic activity was assessed. Key Results: Azithromycin reduced proinflammatory factor production, cell migration, invasion and chemoattraction and enhanced apoptosis, reducing the deleterious inflammatory response of rheumatoid arthritis fibroblast‐like synoviocytes in vitro . Azithromycin ameliorated the severity of collagen‐induced arthritis lesions as efficiently as the TNFα inhibitor etanercept. Transcriptional analyses suggested that azithromycin treatment impairs signalling cascades associated with cholesterol and lipid biosynthesis. GRP78 was identified as a novel target of azithromycin. Azithromycin‐mediated activation of the unfolded protein response via the inhibition of GRP78 activity is required not only for inducing the expression of C/EBP‐homologous protein (ChOP) but also for the activating sterol‐regulatory element binding protein (SREBP) and its targeted genes involved in cholesterol and lipid biosynthetic processes. Furthermore, deletion of GRP78 abolished the anti‐arthritic activity of azithromycin. Conclusion and Implications: These findings indicate that azithromycin can used to treat rheumatoid arthritis.